Architecture and control - Ring, Annie; Steiner, Henriette, 1980-; Veel, Kristin (Architectural intelligences, 2018)
Architecture and Control makes a collective critical intervention into the relationship between architecture, including virtual architectures, and practices of control since the turn of the twentieth to twenty-first centuries. Authors from the fields of architectural theory, literature, film and cultural studies come together here with visual artists to explore the contested sites at which, in the present day, attempts at gaining control give rise to architectures of control as well as the potential for architectures of resistance. Together, these contributions make clear how a variety of post-2000 architectures enable control to be established, all the while observing how certain architectures and infrastructures allow for alternative, progressive modes of control, and even modes of the unforeseen and the uncontrolled, to arise. Contributors are: Pablo Bustinduy, Rafael Dernbach, Alexander R. Galloway, Hans Ulrich Gumbrecht, Maria Finn, Runa Johannessen, Natalie Koerner, Michael Krause, Samantha Martin-McAuliffe, Lorna Muir, Mikkel Bolt Rasmussen, Anne Elisabeth Sejten and Joey Whitfield.